Perception on integrated energy services’ design and management among residents in China - Xiangyu, Xu; Zainordin, Nazatul Syadia; Sharaai, Amir Hamzah; Nik Ab Rahim, Nik Nor Rahimah (Institute of Physics, 2024)
Integrated energy services (IES) in China provide the residents with ef9icient multiple energy supply services through safe and reliable design. The aim of this study is to determine Chinese residents’ perception on IES energy planning and design, as well as the operation and maintenance. By distributing questionnaires to 450 Chinese residents, socio-demographic data, and information on IES design and management were collected. Descriptive analysis was used to summarize the data, while the Mann-Whitney U analysis and Kruskal-Wallis analysis were conducted to identify signi9icant differences between different groups. The results of the descriptive analysis show that residents generally agree with the energy services that IES providers should provide. However, in Tianjin, young people and middle-income residents hold neutral perceptions. The Mann-Whitney U and the Kruskal-Wallis analysis results show that there are signi9icant differences in the perception of IES in gender, marital status, ages, occupations, and income salaries. Gender differences are re9lected in the emphasis on the importance of residents' opinions in energy design and attention to the diverse needs of energy forms; differences in marital status and residents' differences in family life planning; age differences are re9lected in the concern for the innovation and stability of energy services; occupational differences are re9lected in concerns about the rationality and practicality of energy services; while income differences are mainly re9lected in the need for a balance between affordability and quality of energy services. However, educational background did not signi9icantly in9luence respondents' perceptions. Analyzing the perception of different residents on IES and the reasons behind differences can help IES providers improve the quality of energy services and provide residents with more ef9icient and reliable energy services.